RADAR-ES: A Methodological Framework for Conducting Environmental Scans in Health Services Delivery Research - Daniel A. Nagel; Patricia Charlton; Rima Azar; Lilly Koenig; Kara Burns; Terri Kean (Journal of Primary Care & Community Health)
Aim: To propose a methodological framework for conceptualizing, planning, and implementing an environmental scan (ES) in health services delivery research (HSDR). Background: An ES is a methodological approach employed to examine a range of practices, policies, issues, programs, technologies, trends, and opportunities from a variety of data sources to inform program or policy development. Despite the wide use of ESs in health care to inform decision-making, a lack of methodological guidance exists to support researchers in planning and conducting an ES in HSDR. Methods: Adapting McMeekin et al’s process for developing methodological frameworks, we identified literature that described approaches to planning and conducting ESs in addition to exemplar articles that featured ESs in HSDR. We integrated original research findings and synthesized data from all sources to generate an evidence-informed methodological framework. Results: We developed RADAR-ES that consists of 5 phases and is informed by 4 guiding principles: (1) R ecognizing the Issue; (2) A ssessing Factors for ES; (3) D eveloping an ES Protocol; (4) A cquiring and Analyzing the Data; and (5) R eporting the Results. Conclusion: RADAR-ES will provide comprehensive guidance for researchers and health services stakeholders who plan and conduct ESs in HSDR.